Diabetic foot infections: Questions for an infectious disease consultant - Nauriyal, Varidhi; Byers, Karin (Seminars in vascular surgery, 2025)
Diabetic foot infection can lead to limb amputation in approximately 17% of affected patients. Given the complex pathophysiology associated with diabetic foot infection, the goal of limb preservation is best achieved with a multidisciplinary approach and a team of providers including infectious disease consultants. However, these infections often affect populations living in nonmetropolitan areas, where access to an infectious disease physician may be limited. It may fall on the surgeons and primary care providers to not only diagnose infections early, including osteomyelitis, but also facilitate prompt, appropriate antibiotic management. The decision to treat with antibiotics alone versus surgery, choice of antibiotic, route of administration, and duration of treatment are complicated concepts that require a patient-specific approach. In addition, use of oral antibiotics and long-acting lipoglycopeptides has gained prominence and offers an alternate solution to the tedious, resource-intense process of outpatient intravenous antibiotic treatment. The goal of this article is to outline and address diagnostic and management questions that would be posed to an infectious disease consultant. The responses would include a literature review of current management concepts and highlights from the 2023 Infectious Disease Society of America and International Working Group on the Diabetic Foot guidelines.